Defect, transport, and dopant properties of andradite garnet Ca3Fe2Si3O12 - Kuganathan, N.; Sashikesh, G.; Chroneos, A. (AIP, 2020)
There is growing interest to discover suitable calcium containing oxides that can be used as electrode materials in calcium ion batteries. A comprehensive computational investigation of ionic defects and Ca-ion diffusion in Ca-bearing oxide materials at the atomic level is important so as to predict their suitability for use in Ca-ion batteries. In this study, we apply atomistic simulation techniques to examine the energetics of defects, dopants, and Ca-ion diffusion in Ca3Fe2Si3O12. The calculations suggest that the Ca/Fe anti-site defect is the most favorable intrinsic defect causing such significant disorder, which would be sensitive to synthesis conditions. Diffusion of Ca2+ ions within Ca3Fe2Si3O12 is three dimensional, with the activation energy of migration of 2.63 eV inferring slow ionic conductivity. The most favorable isovalent defects are Mn2+, Sc3+, and Ge4+ on Ca, Fe, and Si, respectively, for this process. The formation of extra calcium was considered to increase the capacity and diffusion of Ca in this material. It is found that Al3+ and Mn2+ are the candidate dopants on the Si and Fe sites, respectively, for this process and there is a reduction observed in the activation energies. The electronic structures of favorable dopant configurations are discussed using density functional theory simulations.